PSEUDOACROMEGALY: A CASE OF SEVERE INSULIN RESISTANCE WITH ACROMEGALIC FEATURES AND LOW IGF-1 - Bing, Jordan Hoo Ching; Yee, Sim Sing; Sieng, Florence Tan Hui (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Severe insulin resistance (SIR) is typically associated with well-established metabolic conditions such as central obesity, glucose intolerance, hypertension, dyslipidaemia, and metabolic dysfunction-associated fatty liver disease (MAFLD). We present a case of SIR with prominent dermatologic and acral manifestations mimicking acromegaly, highlighting the importance of recognizing skin and soft tissue changes as possible indicators of underlying insulin resistance. CASE A 35-year-old male with a history of obesity (weight 128.7 kg, height 1.71 m, BMI 44 kg/m²), hypertension (on amlodipine), and hyperlipidaemia (on atorvastatin) was referred for evaluation of hypokalemia (2.35 mmol/L). Clinical examination revealed acromegalic features, including macroglossia, rhinophyma, spade-like hands, and marked dermatologic findings with acanthosis nigricans, pachyderma, multiple epidermoid cysts, and dense axillary skin tags. Visual fields were normal. Anterior pituitary function was normal except for low IGF-1 at 78 ng/mL (normal: 88.3–246 ng/mL). Liver function tests revealed mild abnormalities of bilirubin (51 µmol/L), aspartate aminotransferase 71 U/L (normal: <32 U/L), alanine aminotransferase 23 U/L (normal: <33 U/L), and alkaline phosphatase 136 U/L (normal: 40–129 U/L). The patient denied alcohol use. Fasting insulin was 647 pmol/L (normal: 17.8–173 pmol/L). A diagnosis of pseudoacromegaly secondary to SIR was considered, supported by a significantly elevated HOMA-IR of 27.3 (normal: 0.5–1.4). HbA1c was 8.5%. He was initiated on metformin and lifestyle modification. CONCLUSION This case highlights a rare presentation of SIR with prominent dermatological manifestations mimicking acromegaly. This phenotype of insulin-mediated pseudoacromegaly is thought to arise from a selective post-receptor insulin signaling defect, where metabolic pathways are impaired while mitogenic signaling remains relatively intact. Recognizing these atypical dermatologic clues is vital for early identification of insulin resistance syndromes, enabling timely diagnosis and appropriate intervention.